An analytical study on increasing number of cesarean section in a tertiary care hospital - Dasgupta, Nabanita; Banu, Rezina; Mukherjee, Atasi; Patra, Kajal Kumar; Biswas, Pranab Kumar; Nasrin, Najma (Asian Journal of Medical Sciences, 2023)
Background: One of the most common surgeries performed worldwide is cesarean section (CS). The World Health Organization has identified an ideal CS rate for a nation of around 10–15%. In recent times, the proportion of delivery conducted by CS has increased. However, it can lead to significant increase in maternal and infant morbidity and mortality. Aims and Objectives: This study aims to analyze determine rate of CS and factors that lead to increased number of CS in a tertiary care hospital. Materials and Methods: This analytical prospective study has been carried out on pregnant women undergoing CS in Calcutta National Medical College and Hospital from March 2019 to February 2020. Total 1000 cases undergoing emergency CS during study period were included in the study. Template was generated and analysis was done on SPSS software. Results: In this study, lower segment CS (LSCS) rate is highest in age group of 20–25 years (47.2%), followed by <19 years age group (24%) and lowest LSCS rates seen in >35 years age group. Relationship between parity and LSCS rate is also considered in the present study. Primipara contributes around 76% LSCS rate, where multipara shows only 24% of total LSCS in this study. In respect to total number of LSCS in this study, Robson Group 2B is maximum contributor (37.4%), followed by 2A (14.4%), 4B (13.2%), and Group 6 (7.6%). Conclusion: The LSCS rate in the present study is far higher than standards which are statistically significant also. Hence, it is mandatory to assess risk and benefit ratio of mother and fetus before taking any measure to reduce LSCS rate.